Surface Crack Shape Evolution Modelling using an RMS SIF approach - Chahardehi, Amir Ebrahim; Brennan, Feargal P.; Han, S. K. (Elsevier, 2010)
The majority of fatigue cracks in thick plate and tubular sections in structural components are two-dimensional surface cracks having significant propagation lives before becoming critical. The modelling of surface crack propagation life is important across a range of industries from power generation to offshore so that inspection, maintenance and repair strategies can be developed. Linear Elastic Fracture Mechanics based predictions are commonplace, however, unlike thin sections with associated one dimensional cracks frequently encountered in aerospace industries, crack shape or aspect ratio has a profound effect on crack front Stress Intensity Factor and any resulting Paris Law based life prediction. The two most commonly used approaches are to calculate the crack growth rate at a number of points around the crack front and to consider only surface and deepest points, calculating the relative crack growth rates. Experience using these approaches has shown that the Paris Law co-efficient as determined from plane stress specimens appears not to be applicable to crack growth in both length and depth directions. This paper examines this apparent anomaly, explaining why this discrepancy exists and suggests a practical solution using an RMS SIF approach for surface cracks that negates the need to correct the plane stress Paris law constants.
Keywords: Stress Intensity Factor; RMS SIF; Crack Shape; Crack Aspect Ratio; Paris